Rapid Onset and Resolution of Hydroxychloroquine Cardiomyopathy: A Case Report - Ahmad Ramahi; Amer Heider; J. Michelle Kahlenberg (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is an autoimmune, chronic, and heterogenous disease with organ damage resulting from immune complex deposition and inflammatory infiltrates. Antimalarial drugs, such as hydroxychloroquine (HCQ), are cornerstone immunomodulators for the treatment of SLE. Rarely, HCQ toxicity can occur, leading to devastating outcomes. We report a case of a patient with SLE on HCQ who presented with a rapid onset of large pericardial effusion and a dramatically decreased left ventricular ejection fraction. Endomyocardial biopsy was positive for curvilinear bodies, confirming the diagnosis of hydroxychloroquine cardiotoxicity. Hydroxychloroquine cardiomyopathy is a rare but life-threatening medication side effect. It is important to consider it in any patient taking the medication who presents with a new onset or worsening symptoms of heart failure.